2019
DOI: 10.1111/aogs.13619
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of rectosigmoid endometriosis: A prospective study

Abstract: Introduction: Deep infiltrating endometriosis is a common cause of pelvic pain. However, some patients have limited problems that may be controlled by medical treatment, thus avoiding potentially severe complications to major surgery. This approach requires detailed knowledge on the quality of life and clinical symptoms over time. The aim of the study was therefore to monitor these parameters in patients with rectosigmoid endometriosis treated with oral contraceptives, oral gestagens and /or the levonorgestrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Barra et al [33] [32] reported persistence of pain symptoms in the vast majority of women in whom the nodule regressed or remained stable. On the other hand, Egekvist et al [29] observed that progression of nodule volume dimensions occurred without worsening of symptoms or healthrelated quality of life. Barra et al [33] also confirmed that the increase in endometriotic nodule volume during dienogest therapy was not always associated with worsening of clinical symptoms.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 99%
See 2 more Smart Citations
“…Barra et al [33] [32] reported persistence of pain symptoms in the vast majority of women in whom the nodule regressed or remained stable. On the other hand, Egekvist et al [29] observed that progression of nodule volume dimensions occurred without worsening of symptoms or healthrelated quality of life. Barra et al [33] also confirmed that the increase in endometriotic nodule volume during dienogest therapy was not always associated with worsening of clinical symptoms.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 99%
“…Egekvist et al [29] followed 80 women with rectosigmoid or rectovaginal nodules treated for at least 12 months with a levonorgestrel-releasing intrauterine device (LNG-IUD; n=49), an oral contraceptive (n=12), a progestogen (n=9), or a combination of therapies (n=10). The nodule length and width increased in nine and six patients, respectively.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Possible disease progression of rectosigmoid endometriosis should be monitored 91 ; however, further research is needed to evaluate whether TVS is useful in these cases. 92 If medical treatment fails, surgical therapy may be warranted. From a surgical point of view, it is essential to know the estimated distance from the bowel lesion to the anal verge for estimation of anastomotic height.…”
Section: Rectosigmoidmentioning
confidence: 99%
“…In cases in which medical treatment fails, surgical resection either by discoid resection (DR) or segmental resection (SR) is often the treatment of choice. Surgical treatment of DE affecting the rectosigmoid has been shown to decrease pain, and may be beneficial for fertility [3][4][5][6][7] . Transvaginal sonography (TVS) is a cost-effective, highly accurate and non-invasive tool that is regarded as the first line technique in assessing women with endometriosis, especially when DE is suspected [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%